A SIMULATION BASED STUDY OF ENERGY CONSERVATION OF RESIDENCES IN LAHORE, PAKISTAN - Abid Maan, YASMEEN ABID MAAN; Jameel, Maryam; Dr Munazzah Akhtar (Journal of Arts & Social Sciences, 2021)
A house in composite climate of Lahore (Pakistan) needs intensive cooling in summers; energy recovery ventilation to reduce humidity during monsoon and comfortable indoor temperature during winters. All these conditions have to be fulfilled with a reduced load on energy resources. Recent trends in construction and design of residential buildings in Pakistan symbolize uncontrolled use of energy resources. There is no data available with planning and developing authorities of housing sector that shows an account of energy loads of built houses. The potential of conservation of energy will be analyzed by actually studying the cooling and heating loads of recently constructed housesKey Words: Energy Conservation Potential, Module Study, Simulations